Світова історія у творчій спадщині Тараса Шевченка: спроба історіософського прочитання - Яременко, В.І. (Український історичний журнал, 2007)
У статті аналізується відображення світової історії у творчій спадщині Тараса Шевченка і на основі цього автор конкретизує особливості його історіософії, яка нині є предметом гострих дискусій. The article deals with the depiction of world history in Taras Shevchenko creative heritage. The acguired results are partially compared with study conseguences of his history of Ukraine vision. The author defines the peculiarities of Shevchenko historiography which is nowadays a subject of discussion.